2016
DOI: 10.2807/1560-7917.es.2016.21.2.30109
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant bacteria in unaccompanied refugee minors arriving in Frankfurt am Main, Germany, October to November 2015

Abstract: Many refugees arriving in Germany originate or have travelled through countries with high prevalence of multidrug-resistant Gram-negative organisms. Therefore, all unaccompanied refugee minors (<18 years-old) arriving in Frankfurt am Main between 12 October and 6 November 2015, were screened for multidrug-resistant Enterobacteriaceae in stool samples. Enterobacteriaceae with extended spectrum beta-lactamases (ESBL) were detected in 42 of 119 (35%) individuals, including nine with additional resistance to fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 10 publications
(10 reference statements)
2
48
1
2
Order By: Relevance
“…It is hard to estimate the whether the REF population in the UHF setting is representative of the overall refugee population in Germany. However, a study also conducted in Frankfurt am Main but in unaccompanied refugee minors (<18 years-old) in refugee centres also found a high prevalence of ESBL-producing Enterobacteriaceae (35%) even though lower than that in our study [17].…”
Section: Discussioncontrasting
confidence: 91%
“…It is hard to estimate the whether the REF population in the UHF setting is representative of the overall refugee population in Germany. However, a study also conducted in Frankfurt am Main but in unaccompanied refugee minors (<18 years-old) in refugee centres also found a high prevalence of ESBL-producing Enterobacteriaceae (35%) even though lower than that in our study [17].…”
Section: Discussioncontrasting
confidence: 91%
“…We would like to thank Walter and colleagues for their comment [1] on our respective investigations published in Eurosurveillance [2,3]. While we agree with many of the statements made, we would nevertheless like to clarify the following points:…”
Section: To the Editormentioning
confidence: 67%
“…In addition, colonisation with ESBLproducing bacteria may also be high in some German populations. For example a study among travellers returning to Germany showed colonisation with ESBLproducing Escherichia coli in 30% [3], which is similar to that seen among refugee minors [2]. Screening is, however, not recommended for travellers returning to Germany.…”
mentioning
confidence: 95%
“…To the editor: Two recent publications by Reinheimer et al and Heudorf et al in Eurosurveillance, provided data on multidrug-resistant bacteria obtained from screening of different refugee populations and concluded that additional screening or surveillance for refugees at hospital admission in Germany should be undertaken [1,2]. The high number of people currently migrating to Europe from disaster areas has sparked a debate, whether or not refugees should be screened at hospital admission for colonisation with multidrug-resistant bacteria to limit spread of antibiotic resistance within Europe.…”
mentioning
confidence: 99%
See 1 more Smart Citation